Debated, Deluged or Disappeared: The Flow of Public Discussion Surrounding Drought in FEMA Region 7 - Cory Armstrong; Sharon E. Baldinelli; Kelly Smith; Sharon J Medcalf (Journal of Applied Communications, 2025)
Significant drought conditions existed in 2022 in the four-state FEMA Region 7, which includes Nebraska, Kansas, Iowa and Missouri. Geographically, the four states range from 56,000 square miles (Iowa) and 69,000 square miles (Missouri|) to 77,000 (Nebraska) and 82,000 square miles (Kansas). The terrain includes urban areas, including Kansas City, Des Moines and Omaha, along with large swaths of rural and agricultural areas. Those differences suggest that the needs of different segments of the population may be vastly different. Using the two-step flow of communication theory, this study examines how public officials, opinion leaders and the public discussed drought on social media. We collected and coded social media mentions of drought originating within those states then analyzed how drought effects were discussed and any potential resolution. Results indicated that drought effects were discussed by the public, while current conditions were the focus of posts by officials and opinion leaders. More frequent posts were likely when conditions worsened. Authors recommend targeted discussions by officials in response to public needs.
Keywords: Drought; communication strategies; information sharing; social media